From classroom to clinic: innovating radiotherapy treatment planning education through real-world end-to-end case study simulation with an anthropomorphic phantom - Ioannis Genitsarios; Robin Jhagra; Clive Warn; Jesrina Ann Xavier (BMC Medical Education)
Abstract Background The incorporation of simulation-based learning in healthcare education, particularly in radiotherapy, is necessary for enhancing training and professional competencies to serve patient safety and treatment accuracy. This study aimed to incorporate an innovative end-to-end case study methodology, utilizing an anthropomorphic head phantom, into an undergraduate radiotherapy program at a United Kingdom (UK) based university. The objective was to enhance students’ practical learning and theoretical understanding in radiotherapy treatment planning, a field where precision and accuracy are paramount. Methods The study began with an exploratory literature review to identify key educational challenges and opportunities in radiotherapy treatment planning. A qualitative approach was employed, using a focus group methodology to gather in-depth insights from subject experts, including educational and clinical professionals involved in undergraduate radiotherapy teaching. The focus group discussions explored the integration of an anthropomorphic head phantom within a simulated, case study-based training framework. This innovative approach combined practical skills development with theoretical learning, promoting active engagement and mirroring real-world clinical scenarios. Results Focus group discussions showed favorability towards the end-to-end case study method in simulation-based learning. Participants emphasized evaluating plans through assessments and using supplementary tools like video guides and workbooks to enhance learning. Incorporating the anthropomorphic phantom marked a notable advancement, offering authentic training possibilities in radiotherapy undergraduate education. Conclusions The study demonstrates the potential of integrating an end-to-end teaching concept in radiotherapy education. By providing a realistic and comprehensive training experience, the approach can further enhance student engagement and learning outcomes. While real-world testing is pending, this innovative methodology shows promise in shaping proficient future radiotherapy graduates, highlighting the need for continuous evolution in educational strategies to meet the demands of modern healthcare training.